Pemberdayaan Masyarakat Melalui Inovasi Produk Jamur Tiram Berupa Nugget Jamur Pada Desa Laweyan Kabupaten Probolinggo - Indah Wardani; Taufikurrahman; Mufarrij Al Kahfi; Surya Adinata Putra; Virnanda Cesarila Novanty; Zalzabilla Putri Hartanti (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
In order to provide community service, 11 students from across departments at the Veterans National Development University in East Java carried out the KKNT-MBKM program with the Entrepreneurship and Creative Economy Village scheme located in Laweyan Village, Probolinggo Regency. One of the student work programs is to make product innovations for the Barokah Mushroom UMKM in Ombenan Hamlet, Laweyan Village. The work program was motivated by the problem of the lack of processed oyster mushroom harvests in the Barokah Mushroom SMEs. In addition, there is an opportunity when making oyster mushroom nuggets, such as: lower cost of production, optimizing harvests, frozen food products are more durable, and the high nutritional content of oyster mushrooms also contributed to the idea of ​​making mushroom nuggets. The main purpose of this activity is to overcome the problem of the lack of processed oyster mushroom products in the Barokah Mushroom SMEs. The method of implementing this activity is divided into three stages, namely: (1) surveys and interviews on Barokah Mushroom SMEs, (2) experimenting with oyster mushroom product innovations, and (3) delivering results and steps for making innovation products to Barokah Mushroom SMEs. As a result of these activities, students succeeded in making mushroom nugget product innovations without using preservatives where fried nuggets were suitable for consumption for 8 hours. Meanwhile, nuggets stored in the refrigerator have a shelf life of about one week.